Pseudocercospora griseola Causing Angular Leaf Spot on Phaseolus vulgaris Produces 1,8-Dihydroxynaphthalene-Melanin - Saparrat, Mario (2009)
Pseudocercospora griseolais the causal agent of angular leaf spot of common bean (ALS). It has undergone parallel coevolution with its host and two major groups have been defined, “Andean” (P. griseolaf.griseola) and “Mesoamerican” (P. griseolaf.mesoamericana). The aim of this study was to analyze the nature and the level of the dark pigment synthesized by the representatives of each group. After 21days of incubation on potato dextrose agar medium,P. griseolaf. griseolaisolate S3b developed colonies with diameters of 17.5±1.3mm and concentric rings of pigmentation. Isolate T4 ofP. griseolaf.mesoamericanapresented smaller colonies (9.9±0.3mm) with a uniform dark-gray color. Both isolates, S3b and T4, produced the same pigment, a 1,8-dihydroxynaphthalene-melanin, although different in quantity and structural features as suggested by the IR spectrum. TheP. griseolaf. griseolaisolate S3b had a higher growth rate and melanin content as well as smaller sensitivity to melanin synthesis inhibitors compared to the isolate T4 ofP. griseolaf.mesoamericana. These results suggest a possible link between melanin and growth inP. griseola.